Uwarunkowania transformacji polityki energetycznej Francji. Między ekologiczną modernizacją a ekonomiczną kalkulacją - Młynarski, Tomasz (Rocznik Integracji Europejskiej, 2015)
The project of ecological modernisation – widely integrating all aspects of economic trans- formation – is one of the flagship ideas of incumbent French President François Hollande and the French Socialists. The current energy policy of France, one of the largest global and European energy consumers, is focused on energy efficiency and technological safety standards in the nuclear industry, and to a lesser extent on the development of new green energy technologies. Approaching the German vision of energy transformation, the new French policy has proposed several initiatives for the development of renewable sources. France realised that the development of renewable energy is of strategic importance, not only to meet the energy needs of the country, but also – in the face of the stricter regime of GHG emissions reductions – to provide a competitive advantage for an innovative economy and an opportunity to create many new jobs. Ecological modernisation of the economy is supposed to ensure progress in achieving environmental goals, together with the progress of industrialisation and economic growth (sustainable development).